Preparation of Functional Pasta Supplemented with Amaranth Pregelatinized Extruded Flour - Bello-Pérez, Luis A.; Cabello-Vazquez, Jesus A.; Carmona-Garcia, Roselis-; Patiño-Rodriguez, Omar; Alvarez-Ramirez, Jose (Frontiers in Food Science and Technology, 2022)
Three formulations of semolina pasta supplemented with 50% amaranth flour were studied. Amaranth flour increased protein from 11.7 g/100 g to about 14.0 g/100, dietary fiber from 6.8 g/100 g to about 8.0-10.0 g/100 g. Native amaranth flour deteriorated the texture of cooked pasta by increasing hardness from 15.7 N to 52.8 N and reducing cohesiveness from 0.71 to 0.55. Amaranth flour with 50% and 100% gelatinization degree was explored to reduce the adverse effects of native amaranth flour. The gelatinized amaranth flour mimicked the texture of semolina pasta, although cooking loss increased from 3.3 g/100 g to about 9.2 g/100 g, and the water absorption showed a marked reduction from 116.4% to about 80.0-84.0%. The in vitro starch digestibility was similar for pasta made with semolina and pasta containing gelatinized starch, although pasta made with native amaranth flour decreased from 95% to 85%. Overall, the results showed that amaranth flour offered advantages and drawbacks for pasta formulation with improved nutritional features.